Histomorphological and mucin histochemical study of the alimentary canal of pangas catfish, Pangasius pangasius (Hamilton 1822) - Javd Sadeghinezhad; Hooman Rahmati-Holasoo; Ali Reza Mirzaei; HosseinAli Ebrahimzadeh Mousavi; Narges Zadsar (International Journal of Aquatic Biology, 2017)
The present study describes the histological and mucin histochemical properties of the alimentary canal (AC) of the pangas catfish, Pangasius pangasius. The results revealed that the mucosa of the oesophagus was lined by a stratified epithelium containing chloride cells and taste buds which suggested mechanic, gustatory and physiologic roles of the oesophagus in this species. The stomach mucosa was lined by a simple columnar epithelium. The lamina propria-submucosa in cardiac and fundic stomach contained gastric glands. The pyloric stomach had the thickest muscularis layer among all the parts of the AC. The villi showed the maximum height and width in the middle intestine. The tunica muscularis and serosa showed the thinnest thickness among all parts of AC. The mucin histochemistry showed that the goblet cells of oesophagus and intestine contained both neutral and acidic with carboxylated and sulfated mucins and there was not acidic mucins in epithelial cells of the stomach.